Preliminary results of Moringa oleifera Lam. grown in a semi-arid Mediterranean environment in a climate change scenario - Salsi, Giulia; Greco, Carlo; Laudicina, Vito Armando; Lucia, Caterina; Muscarella, Sofia Maria; Greco, Giuseppe; Orlando, Santo; Fascella, Giancarlo; Mammano, Michele Massimo (Frontiers in Sustainable Food Systems, 2025)
IntroductionClimate change, driven by greenhouse gas emissions, is altering global temperature and precipitation patterns, particularly affecting Mediterranean regions. Adaptation strategies, such as introducing low-input and resilient crops, are essential. Moringa oleifera Lam., a drought-tolerant tree native to north-west India, has emerged as a promising candidate due to its high nutritional value, rapid growth, and adaptability to arid environments.MethodsThis study evaluated the effects of planting methods and spacing on the growth and leaf nutrient composition of M. oleifera in Sicily (southern Italy), a semiarid Mediterranean environment. The experiment was conducted over two growing seasons (2021–2022). In 2021, four treatment plots were tested: two planting methods (seeding, S; transplanting, T) and two spacings (50 cm and 100 cm). In 2022, based on 2021 results, two plots were maintained to assess spacing effects (50 and 100 cm) under transplanting.ResultsTransplanted plants (T) showed higher values than seeded (S) in plant height and biomass production. The T50 treatment reached the highest leaf biomass (15 kg ha−1) and nutrient accumulation. Total nitrogen content was 27 kg ha−1 in 2021 and 125 kg ha−1 in 2022 in T50. Similar trends were observed for phosphorus, calcium, potassium, and magnesium concentrations.DiscussionResults demonstrate that M. oleifera maximizes growth and nutrient uptake when transplanted at 50 cm spacing. This cultivation approach supports its potential as a viable alternative crop in semiarid Mediterranean systems, promoting agricultural diversification and resilience for farmers.